FAKTOR – FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR - Lily Andriani; Suryanto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to examine the factors that influence stock return in manufacturing companies. These factors are return on assets, return on equity, net profit margin, gross profit margin, total asset turnover, current ratio, debt to equity ratio, and firm size. Population of this research are manufacturing companies listed in Indonesia Stock Exchange from 2013-2016. The samples of this study are 153 data using purposive sampling method. This research uses multiple regression method for data analysis. The result of this study shows that return on assets, return on equity, net profit margin, and debt to equity ratio have influence to stock return but gross profit margin, total asset turnover, current ratio, and firm size do not have influence to stock return.